Building with earth: How we are working to revive an ancient, sustainable building technique. Issue 4 (2nd October 2019) - Goodhew, Steve; Carfrae, Jim; Hood-Cree, Karen; Fox, Matthew; Boutouil, Mohamed; Streiff, Francois
Abstract : An international research project led by the University of Plymouth is working to update a centuries-old construction technique for a new generation of energy efficient homes. Whilst it used to be common to build houses with subsoil mixed with straw from local fields, traditional "cob" buildings (or "bauge", in French) now fall foul of strict thermal requirements. Here, the CobBauge team explain how, through their research, they believe they have found a way to update the technique to satisfy French and UK building regulations.